Pemanfaatan Limbah Styrofoam sebagai Bahan Tambah Paving Block - Lydia Riekie Parera; David D.M Huwae; Marchel Nikijuluw (Syntax Corporation, 2023)
This research aims to analyze the effect of styrofoam on the compressive strength value of paving blocks and to analyze the effect of styrofoam on the water absorption value of paving blocks. The benefits of research are that it can reduce pollution and provide solutions for recycling styrofoam waste, providing knowledge and innovation in the use of styrofoam waste as a basic material for making paving blocks and analyzed using trial & error methods. This paving block is made from a mixture of sand, styrofoam, and cement which is made in 3 (three) different mixture composition variations. Variation 1 with a composition of 50% sand and 50% styrofoam without added cement, variation 2 with a composition of 50% sand, 30% styrofoam, and 20% cement, and variation 3 with a composition of 50% sand, 15% styrofoam and 35% cement. This paving block is made with a length of 200mm, width of 100mm, and thickness of 80mm. Testing was carried out referring to the SNI 03-0691-1996 standard. From the test results for variation 1, the average compressive strength value was 15.23 MPa, and the average water absorption value was 0.1134% (quality category C). For variation 2, an average compressive strength value was obtained of 28.32 MPa, and an average water absorption value of 0.0821% (quality category B). Variation 3 obtained an average compressive strength value of 36.72 MPa, and an average water absorption value of 0.0635% (quality category B).